1987
DOI: 10.1002/jcp.1041330203
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and α2‐macroglobulin‐methylamine undergo endocytosis by different mechanisms in rat adipocytes: II. Comparison of intracellular events

Abstract: A previous ultrastructural study showed that gold-labeled insulin (Au-I) and the non-hormonal ligand gold-labeled alpha-2-macroglobulin-methylamine (Au-alpha 2MGMA) underwent endocytosis by dissimilar cell surface structures on rat adipocytes. The present ultrastructural study compared the intracellular routes taken by these two ligands in adipocytes. Intracellular Au-alpha 2MGMA was initially found within apparent coated vesicles but Au-I was not, consistent with the previous demonstration that Au-alpha 2MGMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…14 Studies on insulin entering cells via smooth nonclathrin-coated vesicles, found ligand subsequently co-localised with a marker entering cells via clathrincoated pits. 15 Further studies likewise detected markers, initially entering from coated and non-coated regions, subsequently in common intracellular vesicles. 8,14,16 However, in some situations the intracellular destination of ligand internalised via non-coated regions of the PM differed from that of ligand internalised via coated pits.…”
Section: Historical Perspectivementioning
confidence: 91%
“…14 Studies on insulin entering cells via smooth nonclathrin-coated vesicles, found ligand subsequently co-localised with a marker entering cells via clathrincoated pits. 15 Further studies likewise detected markers, initially entering from coated and non-coated regions, subsequently in common intracellular vesicles. 8,14,16 However, in some situations the intracellular destination of ligand internalised via non-coated regions of the PM differed from that of ligand internalised via coated pits.…”
Section: Historical Perspectivementioning
confidence: 91%
“…Initial interest in caveolae as sites for insulin signaling came from ultrastructural studies of rat adipocytes, which showed that gold-labeled insulin ligand clustered within plasmalemmal caveolae (78,79). Further studies showed that caveolae are highly enriched in adipocytes and that both caveolin-1 mRNA and protein levels increase over 25-fold during the differentiation of mouse 3T3-L1 fibroblasts into adipocytes (an insulin-dependent phenomenon), also suggestive of a role for these microdomains in insulin signaling (215).…”
Section: Glucose Metabolism Insulin Signaling and Diabetesmentioning
confidence: 99%
“…Jarett and co-workers (22) showed that in adipocytes the in-sulin receptor is predominantly localized to plasmalemmal micropinocytotic invaginations (caveolae) that occupied a significant percentage (~13%) of the total plasma membrane. In contrast, coated pits (a more conventional route for endocytosis of receptors) occupied about 0.4 % of the plasma membrane, only about one fifth of the density seen for coated pits in fibroblasts.…”
Section: Caveolae and Signal Transduction By The Insulin Receptormentioning
confidence: 99%
“…Some of these proteins are receptors for ligands (such as folate) that seem to be internalized through caveolae, the process termed potocytosis (1). Other roles of caveolae may include transmembrane signaling, since they contain a number of cellsurface receptor and signal transducing proteins, as judged both by morphological (9,22,36,38,49) and biochemical criteria (9,29,30,42).…”
mentioning
confidence: 99%